Mycobacterium tuberculosis infection induces hypoxic lung lesions in the rat36548 - Heng,Y.; Seah,P.G.; Siew,J.Y.; Tay,H.C.; Singhal,A.; Vanessa Mathys; Kiass,M.; Bifani,P.; Dartois,V.; Herve,M. (Tuberculosis.(Edinb.), 2011)
Hypoxia is believed to influence the metabolic state of Mycobacterium tuberculosis and cause phenotypic drug resistance. Using pimonidazole adduct staining, we show that lung lesions of infected rats contain regions of low oxygen tension. Our results support the use of the rat model for evaluating anaerobic drug activity in vivo
Keywords: 0; Activity; Animals; Anoxia; article; cause; disease; Disease Models,Animal; Diseases; DRUG; Drug Resistance; electronic; Evaluating; Female; Granuloma; im; immunohistochemistry; in vivo; INFECTION; Institute; IS; journal; Lung; microbiology; MODEL; Mycobacterium; Mycobacterium tuberculosis; Nitroimidazoles; Oxygen; pathogenicity; pathology; pharmacology; rats; region; Research; Research Support; resistance; result; results; SB - IM; State; Tension; Tuberculosis; Tuberculosis,Pulmonary; use